2012
DOI: 10.1589/jpts.24.597
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Feasibility of Action Observation Based on Mirror Neuron System on Walking Performance in Post Stroke Patients

Abstract: Abstract.[Purpose] The purpose of this study was to determine the effect of action observation on walking performance and its clinical feasibility for treatment of hemiparetic stroke.[Subjects] The subjects of the study were 30 stroke patients.[Methods] They were randomly allocated to two groups: an experimental group (n=15) which used the action observation training and the control group (n=15) which did no exercise. [Result] The results indicate that step length (cm), stride length (cm), single support time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…(15 min, 5/wk x 4wk) Balance ability: Weight Distribution, Stability Index Gait kinematics: Gait Velocity Lee D. et al [ 26 ] 33 chronic stroke individuals Action observation group: n = 8 (3 F), Age: 63 (SD 3.7) Action practice group: n = 9 (4 F) Age: 62 (SD 1.5) Combination group: n = 9 (4 F) Age: 61 (SD 2.3) Control group: n = 7 (4 F) Age: 60 (SD 5.9) The action observation group watched a video of the task (10 minutes), the action practice group performed the action (10 minutes), the combined action observation-action practice group watched the video of the task (5 minutes) and practiced the action (5 minutes), and the control group did not perform either action observation or action practice. Upper-limb functional dexterity: number of times the full drinking action was performed in one minute Follow up = 1 wk Cowles et al [ 29 ] 29 acute stroke individuals Exp: n = 15 (7 F), Age = 78.8 (SD 8.1) Con: n = 14 (5 F) Age = 75.6 (SD 12.4) Exp: 3 x 8 min imitation of therapist performing functional activities with upper limb (2 x 30 min, 15 consecutive working days) Con: no therapy in addition to conventional physiotherapy Ability to voluntarily contract paretic muscle = MI Functional use of upper limb = ARAT Franceschini et al [ 27 ] 102 sub-acute stroke individuals Exp: n = 53 (20 F) Age = 67.0 (SD 12.4) Con: n = 49 (21 F) Age = 65.7 (SD 11.9) Exp: observation of 3-minute videos of manual tasks (3 videos) + execution of observed movement for 2 minutes (3 times) (2 x 15 min, 5/wk x 4wk) Con: observation of 5 static images displaying objects (3 minutes) + execution of same movement as exp group for 2 minutes (3 times) (2 x 15 min, 5/wk x 4wk) Upper-limb functional dexterity: FAT, BBT, FIMM Motor impairment: FMA Follow up = 4–5 mth Kim JS et al [ 32 ] 30 chronic stroke individuals Exp: n = 15, Age = 64.1 (SD 8.3) Con: n = 15 Age = 65.5 (7.7) Both: 30 min PT Exp: observation of 2-minute videos of walking (5 videos) + walking training for 10 minutes Con: 10 minutes of video in which they were taken through a progressive relaxation program (stretching) Gait kinematics: Spatiotemporal gait parameters (including walking speed) Ertelt et al [ 23 ] 15 chronic stroke individuals Exp: n = 7 (2 F) Age = 57.16 (SD 8.73) Con: n = 8 (2 F) Age = 55.40 (SD 10.77) (90 min x 18 consecutive working days) Exp: observation of 6-minute videos of daily life hand and arm actions (3 videos) + execution of observed movement for 6 minutes (3 times) Con:...…”
Section: Resultsmentioning
confidence: 99%
“…(15 min, 5/wk x 4wk) Balance ability: Weight Distribution, Stability Index Gait kinematics: Gait Velocity Lee D. et al [ 26 ] 33 chronic stroke individuals Action observation group: n = 8 (3 F), Age: 63 (SD 3.7) Action practice group: n = 9 (4 F) Age: 62 (SD 1.5) Combination group: n = 9 (4 F) Age: 61 (SD 2.3) Control group: n = 7 (4 F) Age: 60 (SD 5.9) The action observation group watched a video of the task (10 minutes), the action practice group performed the action (10 minutes), the combined action observation-action practice group watched the video of the task (5 minutes) and practiced the action (5 minutes), and the control group did not perform either action observation or action practice. Upper-limb functional dexterity: number of times the full drinking action was performed in one minute Follow up = 1 wk Cowles et al [ 29 ] 29 acute stroke individuals Exp: n = 15 (7 F), Age = 78.8 (SD 8.1) Con: n = 14 (5 F) Age = 75.6 (SD 12.4) Exp: 3 x 8 min imitation of therapist performing functional activities with upper limb (2 x 30 min, 15 consecutive working days) Con: no therapy in addition to conventional physiotherapy Ability to voluntarily contract paretic muscle = MI Functional use of upper limb = ARAT Franceschini et al [ 27 ] 102 sub-acute stroke individuals Exp: n = 53 (20 F) Age = 67.0 (SD 12.4) Con: n = 49 (21 F) Age = 65.7 (SD 11.9) Exp: observation of 3-minute videos of manual tasks (3 videos) + execution of observed movement for 2 minutes (3 times) (2 x 15 min, 5/wk x 4wk) Con: observation of 5 static images displaying objects (3 minutes) + execution of same movement as exp group for 2 minutes (3 times) (2 x 15 min, 5/wk x 4wk) Upper-limb functional dexterity: FAT, BBT, FIMM Motor impairment: FMA Follow up = 4–5 mth Kim JS et al [ 32 ] 30 chronic stroke individuals Exp: n = 15, Age = 64.1 (SD 8.3) Con: n = 15 Age = 65.5 (7.7) Both: 30 min PT Exp: observation of 2-minute videos of walking (5 videos) + walking training for 10 minutes Con: 10 minutes of video in which they were taken through a progressive relaxation program (stretching) Gait kinematics: Spatiotemporal gait parameters (including walking speed) Ertelt et al [ 23 ] 15 chronic stroke individuals Exp: n = 7 (2 F) Age = 57.16 (SD 8.73) Con: n = 8 (2 F) Age = 55.40 (SD 10.77) (90 min x 18 consecutive working days) Exp: observation of 6-minute videos of daily life hand and arm actions (3 videos) + execution of observed movement for 6 minutes (3 times) Con:...…”
Section: Resultsmentioning
confidence: 99%
“…Imitation of movement is defined as the ability to observe and repeat the behavior of others, and is one of the principal modes of acquiring new patterns of behavior 2 ) . In previous studies of the demonstration and imitation of movement, it has been reported that the difference in the types of imitation models may affect the degree of imitation related to motor control and motor learning 1 , 3 , 4 , 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The results of these previous studies suggest that the accuracy of movement imitation may be affected by the manner in which the demonstration is performed by the PT. This may indicate the importance of the relationship between the type of imitation model used by the PT and the ability to imitate the movement by the patient 4 , 6 , 7 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In a comparison between the two groups, the experimental group showed a significantly greater TUG and 10MWT (dynamic balance indicators) than the control group. A previous study reported that patients after stroke who underwent action observation training showed an improvement of dynamic balance and ambulatory ability 15 ) . In another study, the participants were divided into a self-observation followed by physical training group, a physical training after observing healthy adults’ motions group, and a physical training without observation group.…”
Section: Discussionmentioning
confidence: 94%